2020
DOI: 10.1177/0146167220977709
|View full text |Cite
|
Sign up to set email alerts
|

Is Touch in Romantic Relationships Universally Beneficial for Psychological Well-Being? The Role of Attachment Avoidance

Abstract: Affectionate touch is crucial for well-being. However, attachment avoidance is associated with negative attitudes toward touch. We tested two preregistered hypotheses about how attachment avoidance influences the association between touch in romantic couples and psychological well-being. We examined whether greater attachment avoidance is associated with a reduced link between touch and well-being, and/or whether reduced touch mediates the relationship between attachment avoidance and lower well-being. Across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 57 publications
(87 reference statements)
1
37
0
1
Order By: Relevance
“…present before COVID-19) and future studies should examine this issue. Indeed, past research has shown that attachment avoidance is associated with less frequent touch experience [ 15 ] and it is possible that such effects extend to wanting as well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…present before COVID-19) and future studies should examine this issue. Indeed, past research has shown that attachment avoidance is associated with less frequent touch experience [ 15 ] and it is possible that such effects extend to wanting as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, a particularly effective form of communicating (non-verbal) support, which in addition facilitates the formation and maintenance of social bonds, is touch [8][9][10]. The potential benefits of touch have been studied in many fields, ranging from animal studies to developmental and adult psychological and neuroscientific studies in humans [11][12][13][14][15]. On the one hand, social touch is thought to possess positive hedonic value (although clearly this value depends on the specific context, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overtly affectionate touch may be desired by more and less avoidant people because it is an unambiguous communication of the strength of the emotional bond and may therefore allow avoidantly attached people to “let their guards down” (Girme et al, 2015). Indeed, recent research showed positive associations between overtly affectionate touch and well-being regardless of attachment avoidance level (Debrot et al, 2020). Accordingly, overtly affectionate touch interventions may be more beneficial for avoidantly attached people than casual/playful touch interventions.…”
Section: Discussionmentioning
confidence: 99%